PENERAPAN SISTEM INFORMASI EMOSIONAL MENTAL PROBLEMS (SIEMPRO) DI POSYANDU NGADI ASIH KADIPIRO BANJARSARI SURAKARTA - Ifalahma, Darah; Nurhayati, Nurhayati; Yuliana, Ana; Puspitasari, Rara Ayu (LPPM Universitas Bina Bangsa, 2024)
Ngadi Asih Posyandu is one of the Posyandu for Toddlers in the Kadipiro Village area, Banjarsari District, Surakarta City and is included in the UPT Targeted Area of ​​the Gambirsari Health Center, Surakarta. Posyandu Ngadi Asih has a cadre of 20 people and has implemented 5 posyandu service tables but it is not yet optimal. The initial survey at Posyandu Ngadi Asih Surakarta found children who indicated mental and emotional problems such as impulsive tantrums (fussing with shouting and throwing objects) when their wishes were not met, anger when restricted in using gadgets, hitting their peers, and being reluctant to go to school because they were afraid. The problem found at Posyandu Ngadi Asih was that early detection examinations for mental, emotional and behavioral health had not been carried out. This is due to the limited knowledge and skills of cadres. The root of the problem is that there is no instrument for early detection of mental, emotional and behavioral problems, so that so far at Posyandu Ngadi Asih there has been no recap of data on children who experience mental, emotional and behavioral problems. The solution offered by this program is the Implementation of the Emotional Mental Problems Information System (SIEMPRO). Implementation method with 6 (six) stages, namely preparation, apperception, training, mentoring, evaluation and termination. The results of the program for implementing the Emotional Mental Problems Information System (SIEMPRO) at Posyandu Ngadi Asih have gone well. There was an increase in cadre skills after the activities were carried out, although not completely. Some cadres still need assistance from skilled cadres. The implementation of the Emotional Mental Problems Information System (SIEMPRO) is ready to be implemented at the Ngadi Asih posyandu. The cadres are committed to implementing and applying the results of this program in every posyandu activity and when providing support for Toddler Family Development.